2023
DOI: 10.3390/rs15071842
|View full text |Cite
|
Sign up to set email alerts
|

Learning-Based Traffic Scheduling in Non-Stationary Multipath 5G Non-Terrestrial Networks

Abstract: In non-terrestrial networks, where low Earth orbit satellites and user equipment move relative to each other, line-of-sight tracking and adapting to channel state variations due to endpoint movements are a major challenge. Therefore, continuous line-of-sight estimation and channel impairment compensation are crucial for user equipment to access a satellite and maintain connectivity. In this paper, we propose a framework based on actor-critic reinforcement learning for traffic scheduling in non-terrestrial netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Since the LOS changes with the elevation angle of the satellite, the RL agent constantly retrains to track the everchanging LOS of multiple moving satellites and allows the UE to distribute traffic to the appropriate link(s). However, we found that each time the elevation angle changes, the agent takes a long time to re-train and converge compared to the duration of the satellite visibility [10]. Normally, a moving satellite is visible from a UE near Earth or on Earth for a certain period of time called the satellite visibility period, which can be very short for large constellations.…”
Section: Reference Scenario and Motivationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the LOS changes with the elevation angle of the satellite, the RL agent constantly retrains to track the everchanging LOS of multiple moving satellites and allows the UE to distribute traffic to the appropriate link(s). However, we found that each time the elevation angle changes, the agent takes a long time to re-train and converge compared to the duration of the satellite visibility [10]. Normally, a moving satellite is visible from a UE near Earth or on Earth for a certain period of time called the satellite visibility period, which can be very short for large constellations.…”
Section: Reference Scenario and Motivationsmentioning
confidence: 99%
“…This approach improves the stability of the critic network because the target-critic is updated less often compared to the critic network. The three networks are updated according to equations ( 9), (10), and (12) respectively.…”
Section: ) Rewardmentioning
confidence: 99%